Using Field Experiments to Elicit Risk and Ambiguity Preferences: Behavioural Factors and the Adoption of New Agricultural Technologies in Rural India. - Ward, Patrick S.; Singh, Vartika (Journal of Development Studies, 2015)
We conduct a series of experiments in rural India in order to measure preferences related to risk, loss, and ambiguity. By combining these results with a discrete choice experiment over new and familiar rice seeds, we demonstrate how these behavioural parameters affect decisions to adopt new agricultural technologies, especially when the new technologies are risk reducing. We find that risk averse and loss averse individuals are more likely to switch to new seeds demonstrating risk reducing characteristics, while, contrary to expectations, ambiguity averse individuals are no more willing to retain their status quo than switch to cultivating the new variety.